On the Performance of LTE/Wi-Fi Dual-Mode Uplink Transmission: Connection Probability Versus Energy Efficiency - Zhang, Jing; Han, Jing; Xiang, Lin; Ng, Derrick Wing Kwan; Chen, Min; Jo, Minho (IEEE Transactions on Vehicular Technology, 2020)
This paper evaluates the performance of uplink transmission in an LTE/Wi-Fi coexisting heterogeneous network (HetNet), where user equipments (UEs) capable of jointly performing LTE/Wi-Fi dual access and dual power control have a higher preference in connecting the Wi-Fi access points (WAPs) than the LTE base stations (LBSs). Thereby, each UE competes for Wi-Fi connection using carrier-sense multiple access with collision avoidance (CSMA/CA) and, only if unsuccessful, employs cellular communication. During uplink transmission, the UEs employ truncated channel inversion power control with receiving thresholds adjusted according to the occupied communication modes. Based on the stochastic geometry theory, we derive the analytical expressions for the successful connection probability and the average energy efficiency (EE) of Wi-Fi communications. We show that there exists a maximal successful connection probability for Wi-Fi communications, where the optimal receiving signal and energy thresholds of WAPs depend critically on the density of WAPs. Moreover, the average EE of UEs successfully accessing WAPs saturates in the large receiving signal threshold regime, independent of the density of WAPs. These findings significantly differ from those in cellular communications, where maintaining stable service connection is more emphasized than other operation goals, and reveal that deploying Wi-Fi communication has a potential for improving the EE of the considered HetNet. Both simulation and experiment results validate the analytical derivations. These results together show that, compared with single-mode uplink transmission, the considered dual-mode transmission can achieve higher connection probability and EE simultaneously in LTE/Wi-Fi coexisting HetNets.
CRIS-Team WoS Importer:2020-12-25